25
Results 1 to 2 of 2

Thread: 25

  1. #1
    dj_m.o.h.t.'s Avatar
    Title
    Elite
    Join Date
    Jan 2002
    Posts
    428
    Thanks
    0
    Thanked 0 Times in 0 Posts

    25

    Man zeige: z=e^-kn^2t * sinnx genügt der Wärmeleitungsgleichung zt=kzxx!

  2. #2
    dj_m.o.h.t.'s Avatar
    Title
    Elite
    Join Date
    Jan 2002
    Posts
    428
    Thanks
    0
    Thanked 0 Times in 0 Posts

    Meine Lösung!

    zt = -kn^2 * e^-kn^2t * sinnx

    zx = e^-kn^2t * n * cosnx

    zxx = e^-kn^2t * n^2 * (-sinnx)

    Alle drei zusammen => zt = kzxx

Bookmarks

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •